Influence of countermeasures on the validity of the Concealed Information Test. (24th June 2016) - Peth, Judith; Suchotzki, Kristina; Gamer, Matthias
Abstract: The Concealed Information Test (CIT) is a psychophysiological technique that allows for detecting crime‐related knowledge. Usually, autonomic response measures are used for this purpose, but ocular measures have also been proposed recently. Prior studies reported heterogeneous results for the usage of countermeasures (CM) to corrupt the CIT's validity, depending on the CM technique and the dependent measure. The current study systematically compared the application of physical and mental CM on autonomic and ocular measures during the CIT. Sixty participants committed a mock crime and were assigned to one of three guilty conditions: standard guilty (without CM), physical CM, or mental CM. An additional group of 20 innocents was investigated with the same CIT to calculate validity estimates. Electrodermal responses were more vulnerable for CM usage compared to heart rate and respiration, and physical CM were more effective than mental CM. Independent of CM usage, a combined score of autonomic responses enabled a valid differentiation between guilty and innocent examinees. Fixations and blinks also allowed for detecting crime‐related knowledge, but these measures were more affected by CM application than autonomic responses. The current study delivered further evidence that CM differentially impact physiological and ocular responses in the CIT. Whereas individual data channels were strongly affected by CM usage, a combination of different response measures yielded a relatively stable differentiation of guilty and innocent examinees when mental CM were used. These findings are especially relevant for field applications and might inspire future studies to detect or prevent CM usage in CIT examinations.